JURIDICAL REASONS FOR THE ACCEPTANCE OF THE ACTIO PAULIANA APPLICATION FOR ASSETS ENCUMBERED WITH MORTGAGE RIGHTS IN DECISION NUMBER 461 K/PDT.SUS-BANKRUPT/2019. - TRI MINATI (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2023)
Mortgage rights are born when registered at the National Land Agency office. The panel of judges granted Actio Pauliana’s request by canceling the credit agreement, which also resulted in the imposition of mortgage rights that had been registered. The purpose of the research is to analyze the juridical reasons for granting Actio Pauliana's request in decision number 461K/Pdt.sus-bankruptcy/2019 and to analyze the implications for creditors, namely the Bank. Normative juridical research methods with statutory approaches, conceptual approaches, and case approaches. From the results of the study, it can be concluded that the judge's reason for deciding case Number 461K/Pdt.sus-Bankrupt/2019 based on a marriage agreement that was made was not registered at the Civil Registry Office resulting in the bankruptcy of the property association which has legal implications for creditors to return it to its original state before the credit agreement occurred. PPAT has an important role, namely in the process of checking the data of the parties present along with the documents that are a requirement for making APHT before the registration of collateral rights is carried out.Keywords: Mortgage Rights; Bankruptcy; ActioPauliana.